2001
DOI: 10.1046/j.1445-1433.2001.02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and predictors of axillary lymph node metastases in invasive breast cancer

Abstract: Routine ALND could be omitted in clinically node-negative patients with either a < or = 5-mm, LVI-negative tumour, or a < or = 15-mm tubular or mucinous carcinoma. Axillary lymph node dissection is still useful for determining pathological nodal status in all other cases, and in most cases with palpable ALN, as a therapeutic manoeuvre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
70
3
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 35 publications
14
70
3
5
Order By: Relevance
“…Larger tumor size was found to be an independent predictor of node positive disease in our study, concurring with the data from several other centres [24][25][26] . Previous studies also suggest a significant relationship between tumor size and recurrence free survival.…”
Section: Discussionsupporting
confidence: 81%
“…Larger tumor size was found to be an independent predictor of node positive disease in our study, concurring with the data from several other centres [24][25][26] . Previous studies also suggest a significant relationship between tumor size and recurrence free survival.…”
Section: Discussionsupporting
confidence: 81%
“…higher than breast cancers of any other ERPRHER-2 phenotype (OR = 2.309). Triple positive breast tumours were diagnosed at a younger age and tumour characteristics like tumour size and grade could have been the main reason for this higher probability of ALN involvement [26][27][28][29][30][31][32]. However, the multivariate logistic regression analysis identified ''being triple positive'' as an independent predictor for lymph node involvement.…”
Section: Methodsmentioning
confidence: 81%
“…Controversy also remains regarding the value of steroid receptor expression as a reliable predictor for the ALN status [32]. Some studies reported no value for both ER and PR [27,30] whereas others pointed to a lower risk of ALN metastases for tumours negative for either receptor SE, standard error; OR, odds ratio; CI, confidence interval; LR, likelihood ratio; Df, degrees of freedom; P, P-value a Odds ratio is computed for each 10-year increase in age b Odds ratio is computed for each centimeter increase in size c Odds ratio is computed for each increase in grade [28] or for PR only [26,29,31]. Our findings are in line with these last reports.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] LVI has also been shown to be a predictor of axillary lymph node metastasis. 7,[10][11][12][13] It has been proposed that LVI could be used to identify a subgroup of axillary node-negative patients with an unfavorable prognosis that are likely to benefit from adjuvant chemotherapy. [6][7][8] Furthermore the presence of peritumoral LVI, as assessed on haematoxylin and eosin-(H&E) stained slides, has recently been added to the St Gallen criteria for the selection of adjuvant systemic therapy in operable breast cancer.…”
mentioning
confidence: 99%